2006
DOI: 10.1021/ac052042h
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Structure and Orientation of Organic Molecules Tethered to Flat Graphitic Carbon by ATR-FT-IR and Raman Spectroscopy

Abstract: Mono- and multilayers of nitroazobenzene (NAB), azobenzene (AB), nitrobiphenyl (NBP), biphenyl (BP), and fluorene (FL) were covalently bonded to flat pyrolyzed photoresist films (PPF) by electrochemical reduction of their diazonium derivatives. The structure and orientation of the molecular layers were probed with ATR-FT-IR and Raman spectroscopy. A hemispherical germanium ATR element used with p-polarized light at 65 degrees incidence angle yielded high signal/noise IR spectra for monolayer coverage of molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
89
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 60 publications
9
89
0
Order By: Relevance
“…Current density-voltage (J-V) curves shown are averages of four to eight junctions for a given molecule and thickness from a total of ∼300 fabricated and tested junctions. (19,30,31). The results in Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Current density-voltage (J-V) curves shown are averages of four to eight junctions for a given molecule and thickness from a total of ∼300 fabricated and tested junctions. (19,30,31). The results in Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Different numerical and experimental factors can influence the Raman intensities. Indeed, Anariba et al [58] have shown that despite complex pre-resonance enhancements, the intensity of this band was also strongly correlated to the laser polarization for nitroazobenzene grafted on pyrolyzed photoresist film, while Painelli et al [59] have shown the effect of the solvent and the excitation lines on the relative intensities for [(S)-3-pivaloyloxy-1-(4′-nitro-4-azobenzene)pyrrolidine]. From a numerical point of view, the Raman intensities, as a function of the third derivatives of the energies, are both dependant on the energetic models (basis set truncation, treatment of electron correlation), the methods and the parameters used to calculate the analytical and numerical derivatives [60].…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16] The main aim of this manuscript is to apply a new powerful factor analysis method to the IR spectra of the nitroazobenzene modified GC electrode (NAB-GC) surface, bare GC surface and nitroazobenzene diazonium salt (NAB-DAS) for the structural qualitative characterization of the nanofilm, consisting of the surface of the modified NAB-GC electrode system, in order to test the existence of the nitroazobenzene molecules on the modified GC surfaces.…”
Section: Introductionmentioning
confidence: 99%